Safety effectiveness of pavement design treatment at intersections: Left turning vehicles and pedestrians on crosswalks. (July 2016) - Iasmin, Hasina; Kojima, Aya; Kubota, Hisashi
Abstract: Pedestrians are the most vulnerable road users as they are more exposed than other road users. Pedestrian safety at road intersections still remains the most vital and yet unsolved issue. One of the critical points in pedestrian safety is the occurrence of accidents between left-turning vehicle and pedestrians on crosswalks at signalized intersections. A crosswalk is a place designated for pedestrians and cyclists to cross vehicular roads safely. Drivers are expected to give priority to pedestrians or cyclists during interactions between them on the crosswalk. If a driver exhibits non-yielding behavior, the interaction will turn into a collision. This study examined the safety effect of three crosswalks designed with different materials such as red-colored material or brick pavement based on a safety performance study. The safety performance study considered left-turning driver's gap acceptance behavior and the severity of traffic conflict events between left-turning vehicles and pedestrians. The results of the study indicates that using brick pavement on a crosswalk increases the safety level of the crosswalk. Drivers at such crosswalks are more acquiescent to the priority rule. Highlights: Sharing same signal phase induce conflict between left turn vehicle and pedestrian on crosswalk. We analyze the safety effect of pavement design (red color, brick pavement) on behavior of left turn vehicle on crosswalk. Gap acceptance study and Swedish traffic conflict technique have been used for the analysis. The goal of the present study is to find new countermeasure on crosswalk which will reduce conflict between left turn vehicle and pedestrian.